2020
DOI: 10.1097/pec.0000000000002047
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Upper Extremity Fractures in a Tertiary Care Center in Switzerland

Abstract: Objective: Fractures in children are common and account for 10% to 25% of injuries in children with considerable effects on activity restriction and subsequent high socioeconomically impact. Eighty percent of all fractures in children occur at the upper extremity. The article investigates the epidemiology and fracture pattern of the upper extremity within a pediatric population consulting a tertiary referral hospital in Switzerland.Methods: Study population included all patients younger than 18 years presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
11
0
1
Order By: Relevance
“…When admissions to hospitals due to paediatric orthopaedic injuries are examined, it is seen that these traumas increase during the spring season according to the demographic conditions of the countries. 18 Wang et al 19 reported that the 23.5% prevalence of paediatric orthopaedic trauma admissions in the spring season increased to 27.3% due to the closure of schools in the summer and due to this age group finding more time for sports and social activities. In our study, when groups A1 and B1 (21 March to 31 May) and A2 and B2 (01 June to 31 August) were compared, the prevalence of injury due to outdoor and high-energy traumas in Groups A2 and B2 were significantly higher than Group A1 and B1, respectively (p < 0.05); a finding in parallel to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…When admissions to hospitals due to paediatric orthopaedic injuries are examined, it is seen that these traumas increase during the spring season according to the demographic conditions of the countries. 18 Wang et al 19 reported that the 23.5% prevalence of paediatric orthopaedic trauma admissions in the spring season increased to 27.3% due to the closure of schools in the summer and due to this age group finding more time for sports and social activities. In our study, when groups A1 and B1 (21 March to 31 May) and A2 and B2 (01 June to 31 August) were compared, the prevalence of injury due to outdoor and high-energy traumas in Groups A2 and B2 were significantly higher than Group A1 and B1, respectively (p < 0.05); a finding in parallel to the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The hand is the most frequently injured part of the body in the pediatric and adolescent age group, 1 , 2 with finger fractures being the most common type of hand fracture that occurs in the pediatric population. 3 , 4 Although few data exist on the number of minor finger injuries that require only symptomatic treatment and heal without sequelae they likely account for the majority of all pediatric hand injuries. Significant finger injuries, although rare, must be recognized by the emergency physician since they may cause massive disability in children.…”
Section: Introductionmentioning
confidence: 99%
“…Eighty percent of all fractures in children occur at the upper extremity. [ 5 ] Epidemiology of adult UEF was far less studied, however, some authors suggested that proximal humerus fracture may be associated with increased mortality during the first year after injury, [ 6 , 7 ] and increased mortality was found in patients older than 65 years with distal radius fractures. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Eighty percent of all fractures in children occur at the upper extremity. [5] Epidemiology of adult UEF was far less studied, however, some authors suggested that proximal humerus fracture may be associated with increased mortality during the first year after injury, [6,7] and increased mortality was found in patients older than 65 years with distal radius fractures. [8] Wound infection is one of the most common devastating postoperative complications for all the surgical disciplines, it is reported that surgical site infection (SSI) accounting for 22% of all the social-health related infections.…”
Section: Introductionmentioning
confidence: 99%